International practice of legal support of cyber security of the country - Sozanskyy, Taras; Krasnytskyi, Ivan; Lutsyk, Vasyl Vasylovych; Yaremko, Galyna; Tuz, Nazarii (Allied Business Academies, 2020)
There are systematized and generalized the countries experience on questions of formation and implementation of the state policy of ensuring cyber security on the basis of research of the state policy experience of ensuring cyber security, there are proved necessity of application of administrative influence on processes of ensuring cyber security and revealed possibilities of the adaptation to national circumstances. According to the results of a study conducted among the heads of enterprises and organizations in different countries, it is found that the valuation indicator a cyber attack as an imminent threat, among the leaders: the United States, Australia and Germany. It is determined that over the past ten years, action plans and strategies designed to solve the problem of cyber security have been distributed throughout Europe. It is established that in an environment where cyber threats constantly appear and develop, the state policy of countries is based on flexible, operational strategies of cyber security. The cross-border nature of threats makes the countries to engage in close international cooperation that is due not only need of effective operation to cyber attacks, but the feasibility of timely response, coordinated prevention mechanisms. Attention is focused on the fact that the formation of the national state strategy of cyber security is the basis for the development of effective state policy.

У статті систематизовано та узагальнено досвід країн з питань формування та реалізації державної політики забезпечення кібербезпеки на основі дослідження досвіду державної політики забезпечення кібербезпеки, доведено необхідність застосування адміністративного впливу на процеси забезпечення кібербезпеки та виявлено можливості адаптації до національних обставин. За результатами дослідження, проведеного серед керівників підприємств та організацій різних країн, встановлено, що за показником оцінки кібератаки як безпосередньої загрози серед лідерів: США, Австралія та Німеччина. Визначено, що за останні десять років плани дій та стратегії, спрямовані на вирішення проблеми кібербезпеки, були поширені по всій Європі. Встановлено, що в умовах постійного виникнення та розвитку кіберзагроз державна політика країн базується на гнучких, оперативних стратегіях кібербезпеки.
Keywords: cyber security; legal regulation; strategy; policy; cyber attack; кібербезпека; правове регулювання; стратегія; політика; кібератака